Effects of gender and educational trips instructional strategy on pupils environmental attitude in social studies (2011)
This study assessed the effect of educational trips instructional strategy on primary school pupils' environmental attitude. A pretest-posttest control group quasi-experimental design with a 3x2x2 factorial matrix was used. Participants were 264 primary 5 pupils purposively selected from 12 primary schools in Oyo East, Oyo West, Afijio and Atiba Local Government Areas of Oyo State. Data collected were analysed using Analysis of Covariance (ANCOVA) in testing hypotheses, using pre- test as covariates. The Multiple Classification Analysis (MCA) was used to determine the magnitude of the performance of the various groups. All hypotheses were tested at 0.05 level of significance. The results of the study showed that the treatment significantly had main effect on environmental attitude of pupils. Also, genders do not have significant main effect on environmental attitude of male and female pupils. Implications for curriculum development instructional are presented and recommendations are provided.